Normobaric Hyperoxia Reduces Blood Occludin Fragments in Rats and Patients With Acute Ischemic Stroke. Issue 10 (October 2017) - Shi, Shuhai; Qi, Zhifeng; Ma, Qingfeng; Pan, Rong; Timmins, Graham S.; Zhao, Yongmei; Shi, Wenjuan; Zhang, Yunzhou; Ji, Xunming; Liu, Ke Jian
Abstract : Background and Purpose—: Damage of the blood–brain barrier (BBB) increases the incidence of neurovascular complications, especially for cerebral hemorrhage after tPA (tissue-type plasminogen activator) therapy. Currently, there is no effective method to evaluate the extent of BBB damage to guide tPA use. Herein, we investigated whether blood levels of tight junction proteins could serve as biomarker of BBB damages in acute ischemic stroke (AIS) in both rats and patients. We examined whether this biomarker could reflect the extent of BBB permeability during cerebral ischemia/reperfusion and the effects of normobaric hyperoxia (NBO) on BBB damage. Methods—: Rats were exposed to NBO (100% O2 ) or normoxia (21% O2 ) during middle cerebral artery occlusion. BBB permeability was determined. Occludin and claudin-5 in blood and cerebromicrovessels were measured. Patients with AIS were assigned to oxygen therapy or room air for 4 hours, and blood occludin and claudin-5 were measured at different time points after stroke. Results—: Cerebral ischemia/reperfusion resulted in the degradation of occludin and claudin-5 in microvessels, leading to increased BBB permeability in rats. In blood samples, occludin increased with 4-hour ischemia and remained elevated during reperfusion, correlating well with its loss from ischemic cerebral microvessels. NBO treatment both prevented occludin degradation in microvessels and reduced occludin levels in blood, leading to improved neurological functions in rats. In patients with AIS receiving intravenous tPA thrombolysis, the blood occludin was already elevated when patients arrived at hospital (within 4.5 hours since symptoms appeared) and remained at a high level for 72 hours. NBO significantly lowered the level of blood occludin and improved neurological functions in patients with AIS. Conclusions—: Blood occludin may be a clinically viable biomarker for evaluating BBB damage during ischemia/reperfusion. NBO therapy has the potential to reduce blood occludin, protect BBB, and improve outcome in AIS patients with intravenous tPA thrombolysis. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02974283. Abstract : Supplemental Digital Content is available in the text.